Plant material controls soil organic matter formation and the magnitude of priming effect - Almeida, Luís Fernando Januário (Universidade Federal de Viçosa, 2020)
Soil organic matter (SOM) has the capacity to store large amounts of carbon (C). In this context, SOM is a potential sink of atmospheric C and an alternative for global warming mitigation. Although SOM is widely investigated, the processes governing its formation and retention in soils are not completely understood. Thus, we aimed in the present study to understand how the chemical composition of plant litter drives the formation of new SOM and the mineralization of “native” SOM. The research was divided in two parts that originated two chapters: I) Quantitative parametrization of molecular diversity and microbial respiration of biochemical fractions of eucalypt plant tissues; and II) Forest litter constraints on the pathways controlling soil organic matter formation. For the chapter I we fractionated eucalypt plant components through proximate analysis (PA), which has been widely used to determine litter chemistry in decomposition studies. The fractions obtained had their biochemical composition characterized by 13 C-NMR spectroscopy and thermochemolysis coupled to gas chromatography-mass spectrometry. After this characterization, artificial plant organs were “reconstructed” and incubated in soil samples for 200-days under controlled conditions. Our results showed that the chemical composition of substrate drives the respiration of plant material at the early stages of decomposition. Conversely, at the late stages of decomposition substrate properties had no significant influence on C- CO 2 release. For the chapter II we incubated soil samples with different eucalypt plant organs for 200 days. These plant organs represented forest litter fractions with distinct chemical composition and usual input location in soil (above and belowground). For each treatment, we determined the amount of litter-derived C incorporated into different SOM fractions as well as the priming effect caused by the fresh litter amendments. Our results indicate that the aboveground litter were respired at higher rates but caused less native SOM degradation as compared to root litter. Additionally, aboveground litter contributed to net gains in both POM and MAOM, while root litter only led to net gains in POM. Generally, SOM formation via microbial incorporation of aboveground litter through in vivo pathways appears to be more efficient and causes less degradation of “native” MAOM than roots. Keywords: Substrate biochemistry. Microbial respiration. In vivo pathway. Ex vivo pathway. Priming effect. 13 C-CP/MAS-NMR spectroscopy. Aboveground litter. Root litter. Particulate organic matter. Mineral-associated organic matter.

A matéria orgânica do solo (MOS) tem capacidade para armazenar grandes quantidades de carbono (C). Nesse contexto, a MOS é um dreno potencial para o C atmosférico e uma alternativa para a mitigação do aquecimento global. Embora a MOS seja amplamente investigada, os processos que governam sua formação e retenção nos solos não são totalmente compreendidos. Assim, objetivou-se no presente estudo compreender como a composição química do litter de planta governa a formação da MOS nova e a mineralização da MOS “nativa”. A pesquisa foi dividida em duas partes que originaram dois capítulos: I) Quantitative parametrization of molecular diversity and microbial respiration of biochemical fractions of eucalypt plant tissues; and II) Forest litter constraints on the pathways controlling soil organic matter formation. Para o capítulo I, fracionamos os componentes de plantas de eucalipto por meio de análise proximal (AP), a qual tem sido amplamente utilizada para determinar a composição química do litter em estudos de decomposição. As frações obtidas tiveram sua composição bioquímica caracterizada por espectroscopia de RMN de 13 C e termoquimólise acoplada a cromatografia gasosa e espectrometria de massas. Após essa caracterização, órgãos artificiais de plantas foram “reconstruídos” e incubados em amostras de solo por 200 dias sob condições controladas. Nossos resultados demonstraram que a composição química governa a respiração do material vegetal nos estágios iniciais da decomposição. Por outro lado, nos estágios finais da decomposição, as propriedades do substrato não tiveram influência significativa na liberação de C-CO 2. Para o capítulo II, incubamos amostras de solo com diferentes órgãos de plantas de eucalipto por 200 dias. Esses órgãos representavam frações do litter de florestas de composição química distinta e de diferentes localizações usuais de entrada no solo (acima e abaixo do solo). Para cada tratamento, determinamos a quantidade de C derivado do litter incorporada em diferentes frações da MOS, assim como o efeito priming causado pelo aporte do litter. Nossos resultados indicaram que o litter de parte aérea foi respirado em taxas mais elevadas, mas causou uma menor degradação da MOS nativa comparado com o litter de raiz. Além disso, o litter de parte aérea contribuiu para ganhos líquidos na POM e na MAOM, enquanto o litter de raiz levou a ganhos líquidos apenas na POM. De modo geral, a formação de MOS via incorporação microbiana de litter de parte aérea por meio de vias in vivo parece ser mais eficiente e causar menos degradação de MAOM “nativa” do que raízes. Palavras-chave: Bioquímica do substrato. Respiração microbiana. Rota in vivo. Rota ex vivo. Efeito priming. Espectroscopia 13 C-CP/MAS-NMR. Litter de parte aérea. Litter de raiz. Matéria orgânica particulada. Matéria orgânica associada aos minerais.
O material vegetal controla a formação da matéria orgânica do solo e a magnitude do efeito priming
Keywords: Química do solo; Humus; Respiração microbiana; Análise espectral; Ciência do Solo